Meningkatkan Motivasi dan Hasil Belajar Secara Mandiri menggunakan Metode Interaktif dengan Problem Based Learning pada Materi Aku Pribadi yang Unik di Fase E Kelas X di SMK NEGERI 4 TEBING Tinggi Kec.Padang Hilir - Vina Meloni Br Ginting Manik (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to determine the increase in motivation and cognitive and affective learning outcomes in the independence dimension through the PBL model in students at SMK NEGERI 4 TEBING TINGGI The study is based on a research problem, namely the lack of enthusiasm and motivation of students in learning due to inadequate methods, systems and learning resources, so I took the initiative to use the PBL method so that students are able to collaborate to unite interests and participate in group discussions independently or together. (insert some problems). This type of research is classroom action research with research steps, namely planning, implementation, observation and reflection in each cycle. This study consists of two cycles. The research location at SMK NEGERI 4 TEBING TINGGI for class X students with the material I AM A UNIQUE PERSON The research time was carried out in September 2024. The data collection technique used a learning outcome test and an affective observation rubric for the independence dimension The data analysis technique used a quantitative descriptive technique. The results of the first cycle of research were that 3 students had only 25% success or only 1 person completed and 2 people had not completed 75% ). The results of the cycle II study are that at this cycle meeting there was a significant and very interesting increase because students were able to explore their potential in terms of examining information by watching learning videos and concluding well and structured with good sentences and language. 75% were very good and 25% were good. So this process can be said to be successful in obtaining learning outcomes and motivation if averaged out, it has been towards proficient at the end of cycle 2. In achieving the targeted motivation and learning outcomes of students, they have been able to reach the maximum threshold so that at the cycle 1 meeting it was clear that there were so many changes in students' interests and desires to get lessons that were also quite good, by holding group discussions, students were also able to provide responses independently to demonstrate the results of group discussions, increasing motivation and learning outcomes reaching 93.3%. From the results that exist that the PBL method has a very large influence on the motivation and learning outcomes of students both in terms of group discussions and independently. In the future, the school will implement learning with PBL comprehensively so that the teaching and learning process is more effective and efficient and has its own impression for teachers, especially for students at SMK NEGERI 4 TEBING TINGGI.